PENGEMBANGAN JEJARING BISNIS BERBASIS PRODUK LOKAL KOTA CILEGON - Vadilla Mutia Zahara; Fauji Sanusi; Stannia Cahaya Suci (Universitas Muhammadiyah Malang, 2020)
Micro, Small and Medium Enterprises (MSMEs) are a potential sector for reducing unemployment, increasing income, which in turn has an impact on improving social welfare. One effort to develop MSMEs is to expand business networks, especially MSMEs with local products. The potential of local products such as Ceplis/Emping, palm sugar, Cilegon Batik, and various other typical products is interesting to the public both in Banten and outside Banten province. The technology that is developing at this time, especially the internet and social media, helps businesses to expand their market and business networks, but not a few businesses have not optimized digital technology to expand and develop their business networks. Through this workshop, MSME entrepreneurs are given training and assistance through the use of Google My Business and social media optimization, to help integrate both aspects of marketing both offline and online marketing.